Bilateral interaction between citizens and public authorities: digital rights or digital opportunities - Komarova, Valentina V. (Journal of the Belarusian State University. Law, 2023)
Digitalisation of state and public life directly affects the fulfillment of the constitutional task enshrined as a result of the 2020 reform in the Constitution of Russian Federation which is mutual trust between society and the state. The previously entrenched democracy of statehood has received an additional direction of development, and the pandemic has accelerated the process of digital interaction between people, civil society institutions and a unified system of public power. Firstly, the number of electronic appeals has increased because citizens use the opportunities provided by the achievements of scientific and technological progress with digital forms and methods of appeals to public authorities. Secondly, public authorities introduce new ways of feedback, regulate procedures for interdepartmental and multilateral digital interaction. Thirdly, new types of appeals appear, new procedures for ensuring them. There are new risks in these innovations which are answers to the current demands of our time.
Keywords: constitutional rights; constitutional task; digital forms and methods of appeals; unified system of public authority